2020
DOI: 10.1155/2020/1324348
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Failure of Noninvasive Ventilation in Adult Intensive Care Unit: A Retrospective Clinical Study

Abstract: Background. Noninvasive ventilation (NIV) has been reported to be beneficial for patients with acute respiratory failure in intensive care unit (ICU); however, factors that influence the clinical outcome of NIV were unclarified. We aim to determine the factors that predict the failure of NIV in critically ill patients with acute respiratory failure (ARF). Setting. Adult mixed ICU in a medical university affiliated hospital. Patients and Methods. A retrospective clinical study using data from critical adult pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Predicting NIV failure remains a diagnostic dilemma in general practice. Recent literature shows that patients presenting with acute respiratory failure have an NIV failure rate around 31-50% with nearly 65% of NIV failures occurring within 1-48 h of NIV use (8,(42)(43)(44). Current methods of evaluating for impending NIV failure is based on a multitude of parameters, of which some include monitoring vital signs, evaluating for signs of respiratory distress on physical examination, obtaining arterial blood gas values, calculating severity scores (e.g., SOFA, APACHE II, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting NIV failure remains a diagnostic dilemma in general practice. Recent literature shows that patients presenting with acute respiratory failure have an NIV failure rate around 31-50% with nearly 65% of NIV failures occurring within 1-48 h of NIV use (8,(42)(43)(44). Current methods of evaluating for impending NIV failure is based on a multitude of parameters, of which some include monitoring vital signs, evaluating for signs of respiratory distress on physical examination, obtaining arterial blood gas values, calculating severity scores (e.g., SOFA, APACHE II, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The P/F ratio showed a negative correlation coefficient (r = −0.049), which implies that a better P/F ratio might contribute to survival or improvement in clinical conditions during hospitalization. A study performed by the French Intensive Care Society (Société de Réanimation de Langue Française/SRLF) Trial Group (2018) compared the length of ICU stay of hypoxemic patients (P/F ratio less than or equal to 300 mmHg) with non-hypoxemic patients and found that the median length of ICU stays in the hypoxemic group was approximately twice as long (16 [7-32] vs. 8 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] days, p < 0.001). 24 According to Mammadova, et al (2022), measuring the initial ROX index in patients admitted to the ICU was also helpful in predicting the length of ICU treatment, and the presence of respiratory failure and hypercapnia influenced its cut-off value.…”
Section: Length Of Staymentioning
confidence: 99%
“…2 NIV notably decreases the need for *Corresponding author: oh.liviaroxanne@gmail.com D ORIGINAL ARTICLE intubation and the death rate in patients with pneumoniaassociated respiratory failure in intensive care units (ICUs). 3 NIV failure indicates the need for intubation or mortality. The need for intubation following NIV is associated with elevated heart rate and respiratory rate, a decline in the Glasgow Coma Scale, decreased tissue oxygenation, lower blood pH, longer ICU stay, and higher in-hospital mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although NIV reduces work of breathing and avoids intubation in many patients, the rate of failure of NIV is very high (25-49%). [ 1 ]…”
mentioning
confidence: 99%